Improving The Vocabulary Mastery Through Numbered Heads Together Technique of The Seventh Grade Students of SMP N 5 Baturiti In Academic Years 2015/2016 - Sanjaya, I.D.M.A.W. (Journal of Education Action Research, 2017)
This study aim at: (1) to find out whether Numbered Heads Together can improve studentsâ vocabulary mastery, (2) to find out the response of the students toward the implementation of the strategies. There were two kinds of data (qualitative and quantitative data) which were collected through tests, questionnaire, and writerâs diary. The studentsâ mean score was 4.63% in pretest, 6.2 in posttest 1, and improved became 7.97 in posttest 2. There were no students passed in the pretest, 2 students in the posttest 1, and 18 students in the posttest 2. The result of writerâs diary and questionnaire also showed that the students gave positive response toward the strategies. The results of the questionnaires showed that 18 (90%) of the students admitted that they really like the implementation of Numbered Heads Together. Moreover, 17 (85%) of the students admitted that they were motivated in learning English using Numbered Heads Together.